Lad, a dog: the bad puppy - Lundell, Margo (New York : Scholastic Inc, 1998)
While his mate Lady is ill in the hospital, Lad looks after their puppy Wolf, who gets into a lot of mischievous trouble and even endangers bothe their lives.
"Cartwheel book."
Keywords: Dogs - Juvenile fiction; Dogs - Fiction; Animals-Infancy - Fiction